Efficacy of Crizotinib Combined with Chemotherapy in Treating Advanced Non-Small-Cell Lung Cancer and Effect on Patients' Quality of Life and Adverse Reaction Rate. (10th March 2022) - Ma, Zaiqi; Wang, Yun; Sun, Yonghua; Lin, Gaoyang; Zhao, Zhenqing
Abstract : Purpose . To explore the efficacy of crizotinib combined with chemotherapy in treating advanced non-small-cell lung cancer (NSCLC) and its effect on patients' quality of life (QOL) and adverse reaction rate (ARR). Methods . 90 advanced NSCLC patients admitted to our hospital (from 01, 2019 to 01, 2020) were chosen as the research objects and randomly split into the control group (CG) and experimental group (EG) by flipping a coin, with 45 cases each. Chemotherapy was performed to CG, and the crizotinib treatment was introduced to EG on this basis, so as to compare their clinical efficacy, ARR and 3-year survival rate, and QOL before and after intervention by the Generic Quality of Life Inventory-74 (GQOLI-74). Results . Compared with CG, EG after treatment obtained obviously higher total clinical effective rate (P  < 0.001), lower total ARR (P  < 0.05), higher GQOLI-74 scores (P  < 0.001), and higher 3-year survival rate (P  < 0.05). Conclusion . Combining crizotinib with chemotherapy to advanced NSCLC patients can effectively improve the patients' level of quality of life, prolong the long-term survival rate, and present a better effect than single chemotherapy. Further study is conducive to establishing a better treatment scheme for advanced NSCLC patients.